Formulation of stik from curd protein of ettawa goat (Capraaegagrus hircus) milk with white tofu addition : Formulasi stik dari curd protein susu kambing etawa (Capraaegagrus hircus) dengan subtitusi tahu putih - Fazriah Eva Indriyani; Vivi Nuraini; Merkuria Karyantina (Agrobiotek, 2025)
Stick is a tasty, healthy, and high-protein snack. Goat milk less optimised due to the assumption that goat's milk smells like a goat, so most people don't like to consume it. Tofu is used as a addition for sticks, because tofu is a food that contains the best non-animal protein. The research was purposed to increase consumption of goat milk and white tofu by processing it into milk sticks. In addition, it can also produce milk sticks that are rich in protein and liked by panellists. The experimental design used was a Completely Randomized Disign (CRD) with the first factor being the ratio of curd goat milk and tofu (60%:40%, 50%:50%, 40%:60%) and the second factor being the ratio of wheat flour and tapioca starch (40%:60%, 50%:50%, 60%:40%). The results showed that the substitution of goat milk curd and tofu and the ratio of wheat flour to tapioca starch had a significant effect on characteristics of the milk stick. The best product from several stick formulations in terms of chemical, physical and organoleptic properties is the stick formulation with 60% etawa goat milk curd: 40% white tofu and 60% wheat flour: 40% tapioca starch has a high protein value of 11.51% with a moisture content of 2.27%, ash content of 1.94%, fat content of 32.51%, carbohydrate content by different 51.78%, while etawa goat milk curd sticks with white tofu substitution which has overall level of preffered value of panellists is found in the ratio 3.39 (preferred). Stik from curd protein of etawa goat milk with white tofu be a potensial source of protein.